Work : a deep history, from the stone age to the age of robots - Suzman, James (Penguin Press, 2021)
An anthropological study of the role of work in human evolution challenges deeply held assumptions to explain the different ways our ancient ancestors conducted and regarded work prior to the eras of migration, food production, and city development.